If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(6c+6)=6(7c-9)
We move all terms to the left:
7(6c+6)-(6(7c-9))=0
We multiply parentheses
42c-(6(7c-9))+42=0
We calculate terms in parentheses: -(6(7c-9)), so:We get rid of parentheses
6(7c-9)
We multiply parentheses
42c-54
Back to the equation:
-(42c-54)
42c-42c+54+42=0
We add all the numbers together, and all the variables
96!=0
There is no solution for this equation
| 3(2x+1)=-5(2x-4) | | 2x-4(x-3)=-4+2x+8 | | 11j–5j=18 | | 9-8x=-7x | | 1/2x+17=13 | | 150-125m+43,650=45,675-200m | | -20-2a=-4(-8a-3)-2a | | 3(r+116)-8r=9.5 | | 6=52-2x | | 3x+20+40+2x=180 | | 6(c+4)=c+2 | | -2x=8x+10 | | 12t-24=-36 | | 8x+1=10+7x | | x+1+(x+2)+(x+3)=78 | | 6a+24-9a-19=25 | | 6x+6(x-10)=72 | | 6x+3(2x-11)=17 | | 15+56.45x=58.95 | | -3t-28=-3(t+8)-1 | | 2y=5+6 | | 29-1+x)=-2+3x | | 3-9x=-7-8x | | 2(3n-3)+28=40 | | -225m=1875 | | 3y/2=120 | | .4x+8=24 | | 4x-3=5x+10 | | 5x+8=9x-3 | | 6x+3(x+10)=138 | | 3x2+1−7x=13x2 | | -3(3+3x)=-9 |